2011
DOI: 10.1016/j.addbeh.2010.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal pathways of victimization, substance use, and delinquency: Findings from the National Survey of Adolescents

Abstract: Using a nationally representative sample of 3614 adolescents, age 12 to 17 years, this study examines longitudinal associations among interpersonal victimization (i.e., sexual abuse, physical abuse and/or assault, and witnessed community and domestic violence) and high risk behavior (i.e., alcohol use, drug use, and delinquent behavior). A bidirectional relationship was hypothesized between high risk behavior and victimization for the full sample. Descriptive results indicated that a high correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
120
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 32 publications
12
120
2
3
Order By: Relevance
“…In addition, because the data are cross-sectional, inferences about causality cannot be made; however, youth were asked to reflect on experiences that occurred during specific periods (e.g., before leaving home for child abuse and in the past year for substance use), which assists with temporal ordering of variables. Moreover, it was hypothesized that various forms of abuse and victimization would lead to substance use, and previous research has found support for this ordering of events (Begle et al, 2011;Widom et al, 2006). Despite this, it is also possible that having high rates of substance use may make the young adult an easy target for violence, and thus drinking and/or drug use may lead to physical and/or sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because the data are cross-sectional, inferences about causality cannot be made; however, youth were asked to reflect on experiences that occurred during specific periods (e.g., before leaving home for child abuse and in the past year for substance use), which assists with temporal ordering of variables. Moreover, it was hypothesized that various forms of abuse and victimization would lead to substance use, and previous research has found support for this ordering of events (Begle et al, 2011;Widom et al, 2006). Despite this, it is also possible that having high rates of substance use may make the young adult an easy target for violence, and thus drinking and/or drug use may lead to physical and/or sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on homeless youth and young adults reveals high rates of substance use as well as extensive histories of abuse and victimization, there is a paucity of research among this population that has examined the intersection of these three constructs despite their co-occurrence (see Begle et al, 2011;Lo, Kim, & Church, 2008). As such, the purpose of this article is to examine the relationship between child sexual and physical abuse, street victimization, and partner violence with substance use among a sample of homeless young adults.…”
mentioning
confidence: 99%
“…Efetivamente, sabe-se que um estilo de vida desviante e a manifestação de comportamentos arriscados, como o consumo de drogas, constituem fatores que aumentam o risco de vitimação (Begle et al, 2011;Sampson & Lauritsen, 1990;Zhan, Welte, & Wieczorek, 2001). Por outro lado, estudos mais recentes (Koo, Chitwood, & Sánchez, 2008;MacCoun, Kilmer, & Reuter, 2003) referem a necessidade de se estudar mais profundamente o fenómeno da vitimação do toxicodependente.…”
Section: Introductionunclassified
“…However, the causal direction is both bidirectional and complex. For example, adolescents who are involved in drug use early on are also at higher risk of later exposure to violence (25,26), and there may be other factors that affect the association: " [T]he relationship between childhood abuse and SUPs is not likely to be direct. Several different conditions or disorders have been found to mediate or moderate this relationship, including PTSD, depression, general anxiety symptoms, and conduct problems (2; p.…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%
“…Several studies have established that girls with a history of victimization develop more severe addictive disorders as compared with boys (19,26,30). In addition, a history of sexual abuse is more predictive of alcohol and drug abuse among girls than among boys (17,25). However, some studies have shown that a history of childhood sexual abuse is strongly related to high alcohol consumption among boys (21,29).…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%